Autonomous Wi-Fi Direct connectivity maintenance scheme - Mingyu Joo; Haneul Ko; Yeunwoong Kyung (ICT Express, 2023)
In the emergency situations, Wi-Fi Direct (WFD) can provide group-based communications between group owner (GO) and group members (GMs). However, when GO disappears voluntarily or involuntarily, the group connectivity is terminated. For the re-connection, a group reformation procedure including device discovery, GO negotiation, Wi-Fi protected setup (WPS), and address configuration is needed, which consumes much time. In addition, current WFD requires user intervention to initiate the group reformation. To mitigate this problem, this paper proposes an AWS: an Autonomous WFD connectivity maintenance Scheme. In AWS, GO determines a candidate GO (CGO) in advance and transmits the GO information including addresses and credentials to CGO. When GO disappears, based on the GO information, CGO activates virtual GO (VGO) that can operate exactly the same as the disappeared GO (e.g., with same addresses and operating channel). Simulation results are given to validate AWS and to show the performance of AWS in terms of the group disruption time.